2013
DOI: 10.1186/1475-2875-12-172
|View full text |Cite
|
Sign up to set email alerts
|

Submicroscopic Plasmodium falciparum malaria and low birth weight in an area of unstable malaria transmission in Central Sudan

Abstract: BackgroundMalaria, which frequently occurs in pregnant women in the tropics, is a leading cause of maternal anaemia and low birth weight (LBW) in infants. Few data exist concerning malaria infections that are present at submicroscopic levels during pregnancy and their LBW delivery in babies.MethodsA case–control study (87 in each group) was conducted at the Medani Hospital, Central Sudan. Cases were women who had LBW deliveries where the infants weighed < 2,500 g. Controls were parturient women without having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
59
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(75 citation statements)
references
References 32 publications
12
59
3
1
Order By: Relevance
“…In contrast to many studies in sub-Saharan Africa linking submicroscopic infections with adverse maternal 17,18,20,23 or infant 16,24 outcomes, we did not identify an association between submicroscopic infections and either maternal anemia of any degree or LBW. Women with submicroscopic infections were no more likely to suffer anemia of any severity or to deliver LBW babies than women in whom no parasites were detected by PCR or microscopy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to many studies in sub-Saharan Africa linking submicroscopic infections with adverse maternal 17,18,20,23 or infant 16,24 outcomes, we did not identify an association between submicroscopic infections and either maternal anemia of any degree or LBW. Women with submicroscopic infections were no more likely to suffer anemia of any severity or to deliver LBW babies than women in whom no parasites were detected by PCR or microscopy.…”
Section: Discussioncontrasting
confidence: 99%
“…Submicroscopic infections were linked with maternal anemia in some 17,18,20,23 but not all 12,13,15,21 studies. Similarly, the data are conflicting about the impact of submicroscopic infections on LBW; some studies suggest an increased risk 16,24 in the setting of submicroscopic infections and others no association. [20][21][22][23] Neither study that evaluated preterm birth found an increased risk associated with submicroscopic infection.…”
Section: Introductionmentioning
confidence: 99%
“…However, repeated exposure and acquisition of partial immunity can result in persistent low-grade infection, and although these individuals may not have fever, chronic carriage can result in anaemia, bacterial co-infection and cognitive impairment [15]. In pregnancy, asymptomatic parasitaemia has also been shown to increase the risk of maternal anaemia and the delivery of low birth weight babies [16, 17]. Thus, carriage of asymptomatic parasitaemia potentially has profound implications for the health of individuals and for the control and elimination of malaria [1820].…”
Section: Introductionmentioning
confidence: 99%
“…Malaria during pregnancy can lead to maternal and perinatal adverse effects such as anemia [3] and low birth weight (LBW) delivery [4], the latter of which is the main risk for neonatal and infant morbidity and mortality [5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…In Sudan, malaria is associated with LBW [4], which is a leading cause of high perinatal mortality [11]. The current study was conducted to investigate B and T lymphocytes (using CD 20 and CD3 as markers) and their association- if any- with malarial infection and LBW.…”
Section: Introductionmentioning
confidence: 99%